Scalar radiation emitted from a rotating source around a Reissner-Nordstrom black hole - Crispino, Luis C. B.; da Silva, Andre R. R. [UNESP]; Matsas, George Emanuel Avraam [UNESP] (Amer Physical Soc, 2009)
We investigate the radiation emitted from a scalar source in circular orbit around a Reissner-Nordstrom black hole. Particle and energy emission rates are analytically calculated in the low- and high-frequency regimes and shown to be in full agreement with a numerical calculation. A brief comment connecting the present work with a recent discussion on the cosmic censorship conjecture is included at the end.